2011
DOI: 10.1515/ijamh.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia presenting as pancytopenia in an adolescent girl

Abstract: Iron defi ciency anemia is commonly associated with thrombocytosis and normal leukocyte count. Thrombocytopenia has occasionally been reported in iron defi ciency anemia, but pancytopenia is very rare. We present a case of a young female who presented with iron defi ciency anemia associated with pancytopenia that improved with iron replenishment after initial deterioration, the mechanism of which is also discussed in this case report. This case illustrates two uncommon associations of a very common disease: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
3
15
0
Order By: Relevance
“…Pallor (49%) was the most common physical finding observed followed by splenomegaly (27%) in present study. These findings were comparable to other studies reported from the Indian subcontinent [3,5,6,11,12].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pallor (49%) was the most common physical finding observed followed by splenomegaly (27%) in present study. These findings were comparable to other studies reported from the Indian subcontinent [3,5,6,11,12].…”
Section: Discussionsupporting
confidence: 93%
“…The commonest cause of pancytopenia, reported from various studies throughout the world has been aplastic anaemia. On the contrary most studies conducted in the Indian subcontinent observed megaloblastic anaemia to be the major cause of pancytopenia.However, occasional studies reported from India observed aplastic anaemia as the most common underlying etiology of pancytopenia with megaloblastic anaemia [6,9,11,13,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia may occur in patients with severe IDA who receive iron therapy; however, it is very uncommon [3]. Its pathogenesis remains undetermined but is thought to be related to the alteration in the activity of iron-dependent enzymes involved in thrombopoiesis [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…A single patient with pancytopenia and severe iron deficiency anaemia (Hb-5.5%) showed a micronormoblastic picture on aspiration with erythroid hyperplasia on biopsy and decreased bone marrow iron stores. It has been shown in various studies that iron deficiency presenting with pancytopenia is rare and can be made worse with iron replacement therapy due to decline in leucopoiesis and thromboboiesis [16].…”
Section: Discussionmentioning
confidence: 99%